Kajian Efektivitas Lajur Khusus Sepeda di Jalan L.L.R.E. Martadinata, Kota Bandung - Iscahyono, Achmad Fauzan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
The pandemic has led to an increase in the use of bicycles as a means of transportation that is cheap, environmentally friendly, and has a positive impact on the health of riders. The increase in bicycle users must be in accordance with the availability of adequate facilities and infrastructure to create comfortable and safe cycling activities. This research was conducted to analyze the level of effectiveness of bicycle lanes on L.L.R.E. Martadinata Street, Bandung City. The method used is descriptive, with a quanitative approach. Sampling uses a purposive sampling method for cyclists. The research object was analyzed using observation, questionnaires, and the BLOS (Bicycle Level of Service) method. The results of the BLOS analysis based on the volume factor, speed factor, pavement condition factor, and road cross-sectional factor on the observed bicycle lanes indicate that the service level of bicycle lanes on L.L.R.E. Martadinata Street, Bandung City has a D grade, both on weekdays and weekends. This means that the bicycle lanes are considered ineffective for cyclists from an environmental point of view but is acceptable for experienced cyclists.